PENGARUH MODEL PEMBELAJARAN KLARIFIKASI NILAI TERHADAP SIKAP KEPEDULIAN SOSIAL PESERTA DIDIK DALAM MATA PELAJARAN IPS DI SMP NEGERI 45 PALEMBANG - Dian Yudhistira; Riswan Jaenudin; Fitriyanti Fitriyanti (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This research is entitled "The Effect of Grade Clarification Learning Model towards Students’ Social Concern within Social Science Lesson at SMP Negeri 45 Palembang." The core problem of this research is going to see whether there is effect of Grade Clarification Learning Model towards Students’ Social Concern within Social Science Lesson at SMP Negeri 45 Palembang. The population of this this research are the students of class VIII consisting of 286 students and the samples are taken by using the techniques of Cluster Random Sampling and obtained class VIII 2 as samples totaling 40 learners. This study uses research methods form Pre-Experimental Design with design studies One-group pretest posttest. Data collection techniques in research using questionnaire and observation. The statistics are used to analyze the data in statistical parametric verification is through a hypothesis test (t-test) using t-test formula product moment and significance level (α) = 5% and df = n-2. From the hypothesis testing results obtained t = 46.56> table = 1.686 then Ho is rejected and Ha accepted. This shows that there is a learning model values clarification influence on the attitudes of social awareness of learners in social studies in SMP 45 Palembang. Therefore, it is advisable for teachers to implement learning model truth-values in social studies learning as an alternative to improve the caring attitude social learners.